Inari Amertron Berhad / Nur Atikah Ismail ... [et al.] - Ismail, Nur Atikah; Azri, Nur Azra Hanim; Nor Azman, Nur Athirah; Abdul Halim, Nur Fatin Allya; Mohd Saufian, Nur Intan Solihah (2019)
The economy analysis is used to examine economic factors that influence the entire market enhances also affects the price of an individual stock. The economic factors that we used to analyst the country are Growth Domestic Product (GDP), interest rate, inflation rate, and unemployment rate. An economic analysis is divided into four groups which are developed countries, developing countries (Asia), third world countries, and domestic country. The developed country that we choose is Italy, Germany, United States, Japan, and China. Developing countries that we choose are Indonesia, Singapore, Vietnam, Brunei, and Thailand. Third world country is Nepal, Bangladesh, and Sudan. The domestic country is Malaysia.